Արցախի Հանրապետության էներգահամակարգում գազատուրբինային կայանքների օգտագործման տեխնիկատնտեսական հիմնավորումը - Ստեփան Ռաֆիկի Պապիկյան (ՀՀ ԳԱԱ հրատ.)
В статье предлагается в энергосистеме Арцаха использовать газотурбинние установки. Технически возможно и экономически целесообразно для экономии топлива в г. Степанакерте построить ТЭЦ с использованием газотурбииних установок мощностью 50МВт. Для разных вариантов подсчитаны приведенные затраты.The article proposes to utilize the gas-turbine stations in the power system of the Republic of Artsakh. It is technically possible and economically feasible to build a combined heat and power plant with a capacity of 50 megawatt in Stepanakert that utilizes gas turbine stations. Various estimates are provided based on the costs presented in the article.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ